PENERAPAN PENDEKATAN RULE OF REASON OLEH KPPU DALAM PENYALAHGUNAAN POSISI DOMINAN - Rr Ani Wijayati; Adrianus Herman Henok; Poltak Siringoringo (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2024)
This research aims to analyze the application of the rule of reason approach in the abuse of a dominant position and the authority of the KPPU in applying the rule of reason in the abuse of a dominant position. The method used is normative juridical research. The results of this research show that the KPPU in assessing Article 25 of Law No. 5 of 1999 alternatively uses one of the two per se illegal or rule of reason approaches with the aim of efficiency, innovation and consumer welfare